2017
DOI: 10.5194/esd-2017-83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability Ensemble Averaging of 21st century projections of terrestrial net primary productivity reduces global and regional uncertainties

Abstract: Abstract.Multi-model averaging techniques provide opportunities to extract additional information from large ensembles of simulations. In particular, present-day model skill can be used to evaluate their potential performance in future climate simulations. Multi-model averaging methods have been used extensively in climate and hydrological sciences, but they have not been used to constrain projected plant productivity responses to climate change, which is a major uncertainty in earth system modelling.Here, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This suggests that further model developments are likely needed to address structural uncertainties and missing processes, which will then need to be followed up with additional parameter DA experiments to ensure increasing complexity does not degrade model skill (Famiglietti et al., 2021). We know for example that certain important processes for sparsely vegetated, mixed shrub‐ and grass‐dominated dryland ecosystems, such as wildfires (Exbrayat et al., 2018; Lasslop et al., 2016; Whitley et al., 2017) and biological soil crust C cycling (Belnap et al., 2016), are currently not represented in most TBMs. Exbrayat et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that further model developments are likely needed to address structural uncertainties and missing processes, which will then need to be followed up with additional parameter DA experiments to ensure increasing complexity does not degrade model skill (Famiglietti et al., 2021). We know for example that certain important processes for sparsely vegetated, mixed shrub‐ and grass‐dominated dryland ecosystems, such as wildfires (Exbrayat et al., 2018; Lasslop et al., 2016; Whitley et al., 2017) and biological soil crust C cycling (Belnap et al., 2016), are currently not represented in most TBMs. Exbrayat et al.…”
Section: Discussionmentioning
confidence: 99%
“…Exbrayat et al. (2018) showed using a Bayesian parameter DA experiment that model simulations with fire had faster carbon turnover times and increased C allocation to wood and root pools (rather than foliage) than the simulations without fire–all of which resulted in changes to GPP, net primary productivity, biomass and carbon use efficiency. Their results neatly demonstrate that errors due to missing model processes can be aliased onto the posterior parameter values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CARbon DAta-MOdel fraMework (CARDAMOM; e.g., Bloom et al, 2016;Yin et al, 2020;Exbrayat et al, 2018;Smallman et al, 2017;López-Blanco et al, 2019;Famiglietti et al, 2021;Bloom et al, 2020;Yang et al, 2021a) uses carbon cycle and meteorolog-ical observations to constrain carbon fluxes, states and process controls represented in the DALEC2 model of terrestrial C cycling (Williams et al, 2005;Bloom and Williams, 2015). Specifically, CARDAMOM uses a Bayesian model-data fusion approach to optimize DALEC2 time-invariant parameters (such as leaf traits, allocation and turnover times) and the "initial" C and H 2 O conditions (namely biomass, soil and water states at the start of the model simulation period).…”
Section: The Cardamom Model-data Fusion Systemmentioning
confidence: 99%
“…Terrestrial vegetation is an important part of the global ecosystem, and is closely related to biodiversity. Terrestrial vegetation in ecosystems experiences severe changes due to global warming [3]. The five consecutive assessment reports from the Intergovernmental Panel on Climate Change (IPCC) (1990, 1995, 2001, 2007 and 2013) have all shown that global warming is unquestionably occurring, and that regions at high latitudes and high altitudes have been the most sensitive to that change [4].…”
Section: Introductionmentioning
confidence: 99%